Eksplorasi Biaya Non Fisik Pada Tahap Penilaian Pengadaan Tanah Bagi Pembangunan untuk Kepentingan Umum Berdasarkan Peraturan Pemerintah Republik Indonesia Nomor 19 Tahun 2021 Tentang Penyelenggaraan Pengadaan Tanah: (studi Kasus Penilaian Pengadaan Tanah Short Cut Singaraja) - I Gede Adiratma (Public Inspiration : Jurnal Administrasi Publik, 2022)
Government Regulation of the Republic of Indonesia Number 19 of 2021 concerning the Implementation of Land Procurement for Development in the Public Interest article 68 mentions that the assessment of the amount of Indemnity of fields per plot of land, consisting of elements: a.land; b. Upper Ground And Basement; c. building; d. plants; e. objects related to the land; and/or f. other losses that can be assessed. Components e and f often cannot be estimated nominally. This paper aims to explore the amount of components E and F in case studies The fair replacement value of short cut collateral in Gitgit village, Sukasada Subdistrict, Buleleng Regency of Bali Province in 2021. This paper used an exploratory approached with data collected by public works service, spatial planning, housing and residential areas of Bali province. It was found that the E and F components reached 3,35%. Components E and F are categorized as total non-physical values in which include Premium value, solatium, moving costs and upakara costs.The cost of upakara in this case study amounted to 17% of the total percentage of non-physical costs.